Carolingian commentaries on the Apocalypse by Theodulf and Smaragdus - Gumerlock, Francis X.; Gumerlock, Francis X.; Theodulf, Bishop of Orléans, approximately 760-821; Smaragdus, Abbot of St. Mihiel, active 809-819 (Commentary series., 2019)
"In the early ninth-century Theodulf of Orleans and Smaragdus of Saint Mihiel served as advisers to Charlemagne. This book provides English translations of a Latin commentary on the Apocalypse written by Theodulf and three homilies on the Apocalypse by Smaragdus. A comprehensive essay introduces these texts, their authors, sources, and place in ninth-century biblical exegesis"--